Actuators (IntechOpen, 2023)
The book promotes new research results in the field of modern actuators and their applications. New coverage of dielectric barrier discharge plasma actuators, polymeric microgripper based on the cascaded V-shaped electrothermal actuators, ionic polymer actuators, wideband actuators and energy harvesters, electromagnetic actuators and shape memory alloy actuators are comprehended. The book is structured in four sections: design, fabrication and simulation; control systems; medical applications and fault detection. Seven chapters are published following a rigorous selection process. In the first section, a study carried out to investigate experimentally and by numerical simulations a microscale plasma actuator; the design, fabrication, numerical simulations, and experimental investigations of a polymeric microgripper designed using the cascaded V-shaped electrothermal actuators; a review of the development of ionic polymer actuator with introduction of two kinds of typical polymer actuators - ionic polymer-metal composites and bucky gel actuator - with their basic principle and fabrication process and typical applications and a methodology of designing and testing wideband actuators and energy harvesters, treated as one mechanical resonator, with a discussion on shock harvester, resonant harvester and energy transmission system, are presented. The second section has a chapter dedicated to modeling, system identification and control of electromagnetic actuators with main focus on the actuators used in magnetic levitation, in fuel injection systems and in variable valve timing. The third section presents a study focused on quantifying the decline in tactile sensation associated with diabetic neuropathy and developed a measurement device that used a thin-shaped memory alloy wire as the actuator. The fourth section includes a chapter presenting a two-level fault diagnosis and root-cause analysis scheme for a class of interconnected invertible dynamic systems, which aims at detecting and identifying actuator fault and causes.